Mineral bone disorders and kidney disease in hospitalized children with sickle cell anemia - Batte, Anthony; Kasirye, Philip; Baluku, Reagan; Kiguli, Sarah; Kalyesubula, Robert; John, Chandy C.; Schwaderer, Andrew L.; Imel, Erik A.; Conroy, Andrea L. (Frontiers in Pediatrics, 2023)
Background Mineral bone disorders (MBD) are common in sickle cell anemia (SCA). Frequent vaso-occlusive crises (VOC) further impact MBD in children with SCA. We evaluated the prevalence of markers of SCA-related MBD (sMBD) in hospitalized children and assessed the relationship between sMBD and individual mineral abnormalities with kidney disease. Methods We prospectively recruited 185 children with SCA hospitalized with a VOC. Serum measures of mineral bone metabolism (calcium, phosphate, parathyroid hormone, 25-hydroxy vitamin D, FGF23, osteopontin) were measured at enrollment. The primary outcome was markers of sMBD defined as a composite of hypocalcemia, hyperphosphatemia, hyperparathyroidism, or deficiency in 25-OH vitamin D. Secondary outcomes included individual abnormalities in mineral metabolism. The Kidney Disease: Improving Global Outcomes (KDIGO) guidelines were used to define SCA-associated acute kidney injury (AKI). AKI was further assessed using urine NGAL as a marker of tubular injury. Acute kidney disease (AKD) was defined as a composite of AKI, an eGFR < 90 ml/min per 1.73 m2 using the Cystatin C GFR equation, or evidence of structural injury (positive biomarker test or albuminuria). Results The mean age of children was 8.9 years and 41.6% were female. The prevalence of sMBD was 47.6%, with hypocalcemia the most frequent abnormality (29.9%, 55/184) followed by hyperphosphatemia (20.7%, 38/184), hyperparathyroidism (8.7%, 16/185), and vitamin D deficiency (5.4%, 10/185). There was no association between sMBD and sKDIGO-defined AKI using serial changes in creatinine or when incorporating biomarkers to define AKI. However, the presence of AKD was associated with a 2.01-fold increased odds of sMBD (95% CI 1.05 to 3.83) and was driven by a decrease in eGFR (OR, 2.90 95% CI: 1.59 to 5.29). When evaluating individual mineral abnormalities, hypocalcemia was associated with AKD and low eGFR while hyperparathyroidism was associated with low eGFR, AKI and structural injury. Vitamin D deficiency was associated with structural kidney injury. Vitamin D deficiency, hyperparathryoidism, and increases in FGF23 and osteopontin predicted mortality (p < 0.05 for all). Conclusion MBD is common among children with SCA hospitalized with VOC. Biomarkers of kidney injury and bone health may help risk stratify children at risk of sMBD. Routine evaluation of sMBD in children with SCA may improve long-term bone health.